Parallel, distributed, and pervasive computing - Hurson, A. R. (Amsterdam ; Boston : Elsevier Academic Press, 2005)
The term computation gap has been defined as the difference between the computational power demanded by the application domain and the computational power of the underlying computer platform. Traditionally, closing the computation gap has been one of the major and fundamental tasks of computer architects. However, as technology advances and computers become more pervasive in the society, the domain of computer architecture has been extended. The scope of research in the computer architecture is no longer restricted to the computer hardware and organization issues. A wide spectrum of topics ranging from algorithm design to power management is becoming part of the computer architecture. Based on the aforementioned trend and to reflect recent research efforts, attempts were made to select a collection of articles that covers different aspects of contemporary computer architecture design. This volume of the Advances in Computers contains six chapters on different aspects of computer architecture. Key features: - Wide range of research topics. - Coverage of new topics such as power management, Network on Chip, Load balancing in distributed systems, and pervasive computing. - Simple writing style. Wide range of research topics. Coverage of new topics such as power management, Network on Chip, Load balancing in distributed systems, and pervasive computing. Simple writing style.
Contributors. -- Preface. -- 1. Techniques to Improve Performance Beyond Pipelining: Superpipelining, Superscalar, and VLIW, (J.-L. Gaudiot, J.-Y. Kang, W.W. Ro). -- 2. Networks on Chip (NoC): Interconnects of next generation Systems on Chip, (T. Theocharides, G.M. Link, V. Narayanan, M.J. Irwin). -- 3. Characterizing Resource Allocation Heuristics for Heterogeneous Computing Systems, S. Ali, T.D. Braun, H.J. Seigel, A.A. Maciejewski, N. Beck, L. Boloni, M. Maheswaran, A.I. Reuther, J.P. Robertson, M.D. Theys, B. Yao) . -- 4. Power Analysis and Optimization Techniques for Energy Efficient Computer Systems, (W. Chedid, C. Yu, B. Lee) . -- 5. Flexible and Adaptive Services in Pervasive Computing, (B.Y. Sung, M. Kumar, B. Shirazi) . -- 6. Search and Retrieval of Compressed Text, A. Mukherjee, N. Zhang, T. Tao, R.V. Satya, W. Sun).
Includes bibliographical references and index.
Keywords: Computer architecture; Microprocessors -- Design and construction; System design; Electronic books